Investigation of the hemodynamic effect of stent wires on renal arteries in patients with abdominal aortic aneurysms treated with suprarenal stent-grafts - Sun, Zhonghua; Chaichana, Thanapong (My University, 2009)
The purpose of the study was to investigate the hemodynamic effect of stent struts (wires) on renal arteries in patients with abdominal aortic aneurysms (AAAs) treated with suprarenal stent-grafts. Two sample patients with AAA undergoing multislice CT angiography pre- and postsuprarenal fixation of stent-grafts were selected for inclusion in the study. Eight juxtarenal models focusing on the renal arteries were generated from the multislice CT datasets. Four types of configurations of stent wires crossing the renal artery ostium were simulated in the segmented aorta models: a single wire crossing centrally, a single wire crossing peripherally, a V-shaped wire crossing centrally, and multiple wires crossing peripherally. The blood flow pattern, flow velocity, wall pressure, and wall shear stress at the renal arteries pre- and post-stent-grafting were analyzed and compared using a two-way fluid structure interaction analysis. The stent wire thickness was simulated with a diameter of 0.4, 1.0, and 2.0 mm, and hemodynamic analysis was performed at different cardiac cycles. The interference of stent wires with renal blood flow was mainly determined by the thickness of stent wires and the type of configuration of stent wires crossing the renal ostium. The flow velocity was reduced by 20-30% in most of the situations when the stent wire thickness increased to 1.0 and 2.0 mm. Of the four types of configuration, the single wire crossing centrally resulted in the highest reduction of flow velocity, ranging from 21% to 28.9% among three different wire thicknesses. Wall shear stress was also dependent on the wire thickness, which decreased significantly when the wire thickness reached 1.0 and 2.0 mm. In conclusion, our preliminary study showed that the hemodynamic effect of suprarenal stent wires in patients with AAA treated with suprarenal stent-grafts was determined by the thickness of suprarenal stent wires. Research findings in our study are useful for follow-up of patients treated with suprarenal stent-grafts to ensure long-term safety of the suprarenal fixation. © 2009 Springer Science+Business Media, LLC.
Keywords: Abdominal aortic aneurysm; Blood flow; Flow velocity; Renal ostium; Simulation; Suprarenal stent-graft